Iowa Birdline update, April 12, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email for the Iowa Birdline update for April 12, 1993. Highlights of the update include sightings of Sandhill Cranes, a Cinnamon Teal and a Black-throated Sparrow. Also included are handwritten notes for the next week's update with sightings of an adult Iceland Gull in a field with about 300 Ring-Billed Gulls. Epson - sheet feed/flatbed